Smart Route Planning Using Open and Participatory Data - CLARKE, SIOBHAN; NALLUR, VIVEK (My University, 2015)
Smart cities are not merely the infusion of technology into a city's infrastructure, but also require citizens interacting with their urban environment in a smart and informed manner. Transportation is key aspect of smart cities. In this paper, we present a smart route planning open-source system; SMART-GH utilizes open data and participatory sensing, where citizens actively participate in collecting data about the city in their daily environment, e.g., noise, air pollution, etc. SMART-GH then augments the routing logic with sensor data to answer queries such as `return the least noisy route'. SMART-GH enables citizens to make smarter decisions about their daily commute, and subsequently improve their quality of life.
Proceedings of 11th International Conference on Open Source Systems
PUBLISHED
Florence, Italy
Keywords: Computer Science/Engineering; Distributed Systems; Software Engineering